An Analysis of Moral Values Found in K-drama “Flower of Evil” - Vebrianti Umar; Elsa Rosalina; Rahma Pitria Ningsih; Nasrullah; Hidayah Nor (Universitas Nusantara PGRI Kediri, 2023)
A literary work is a representation of human thought that has been poured into a medium. The literary works classified as informative literature or imaginative literature. Informative literature focuses on facts, history, explanations, and famous people, whereas imaginative literature is based on fantasy and employs connotative language and qualified aesthetic art. Moral values are the values than can give the readers or viewers some positives message from literary works. This article tries to analyze the K-Drama entitled Flower of Evil. Flower of Evil is one of the most popular K-drama that aired in TVN (One of television station in South Korea) on Wednesday and Thursday from July to September 2020. This drama has got 57th Baeksang arts award for the best director in 2020. Baeksang arts award is one of the precious award in South Korea especially in entertainment industrial. This research uses qualitative method because the researchers try to describe the moral values from the K-Drama Flower of Evil. Documentation method is used for collecting the data of this research. The data analysis method is an important step in this research because it examines the validity and reliability of the data collections. The results of this research are the researchers have found out sixth moral values in this K-Drama. First, don’t judge the people just based on their appearance. Second, making your own reputation as a “good person” is important in today’s society. Third, father is the first love for his daughter. Fourth, family is always together, no matter how far you go family is still the most comfortable place to come home from all of the problems. Fifth, your family is the one who know you better than the other people. Last, the truth will always win. Keywords: Analysis; Flower of Evil; K-Drama; Moral Values